Depletion of Lipid Efflux Pump ABCG1 Triggers the Intracellular Accumulation of Extracellular Vesicles and Reduces Aggregation and Tumorigenesis of Metastatic Cancer Cells - Namba, Yuri; Sogawa, Chiharu; Okusha, Yuka; Kawai, Hotaka; Itagaki, Mami; Ono, Kisho; Murakami, Jun; Aoyama, Eriko; Ohyama, Kazumi; Asaumi, Jun-ichi; Takigawa, Masaharu; Okamoto, Kuniaki; et al. (Frontiers in Oncology, 2018)
The ATP-binding cassette transporter G1 (ABCG1) is a cholesterol lipid efflux pump whose role in tumor growth has been largely unknown. Our transcriptomics revealed that ABCG1 was powerfully expressed in rapidly metastatic, aggregative colon cancer cells, in all the ABC transporter family members. Coincidently, genetic amplification of ABCG1 is found in 10% to 35% of clinical samples of metastatic cancer cases. Expression of ABCG1 was further elevated in three-dimensional tumoroids (tumor organoids) within stemness-enhancing tumor milieu, whereas depletion of ABCG1 lowered cellular aggregation and tumoroid growth in vitro as well as hypoxia-inducible factor 1α in cancer cells around the central necrotic areas in tumors in vivo. Notably, depletion of ABCG1 triggered the intracellular accumulation of extracellular vesicles (EVs) and regression of tumoroids. Collectively, these data suggest that ABCG1 plays a crucial role in tumorigenesis in metastatic cancer and that depletion of ABCG1 triggers tumor regression with the accumulation of EVs, their derivatives and cargos, implicating a novel ABCG1-targeting therapeutic strategy by which redundant and toxic substances may be accumulated in tumors leading to their regression.